U-Pb ages of detrital zircon from Cenozoic sediments in the southwestern Tarim Basin, NW China: Implications for Eocene–Pliocene source-to-sink relations and new insights into Cretaceous–Paleogene magmatic sources. (1st May 2018) - Yang, Wei; Fu, Ling; Wu, Chaodong; Song, Yan; Jiang, Zhenxue; Luo, Qun; Zhang, Ziya; Zhang, Chen; Zhu, Bei
Graphical abstract: Highlights: New detrital zircon ages from the southwestern Tarim Basin range from 45 to 65 Ma. Two major changes in source-to-sink relationship occurred since the Middle Eocene. Connection may exist between the central-south Pamir salient and basin continuously. Abstract: A detailed investigation of potential provenance is still lacking in the southwestern Tarim Basin, which restricts our complete understanding of Cenozoic source-to-sink relations between the basin interior and the Pamir salient - western Kunlun Mountain Range. Debate also exists concerning the potential sources of the Paleogene and Cretaceous igneous detritus present in the Cenozoic sedimentary sequences. Here, we present U-Pb (LA-ICP-MS) ages of detrital zircons from the continuous Eocene-Pliocene sediment series in the well-exposed Aertashi section to investigate changes in sediment provenance through time. The U-Pb detrital zircon ages range widely from 45 to 3204 Ma and can be divided into seven main groups: 45–65 Ma (sub-peak at 49 Ma), 67–103 Ma (sub-peak at 95 Ma), 196–251 Ma (sub-peak at 208 Ma), 252–416 Ma (sub-peak at 296 Ma), 417–540 Ma (sub-peak at 446 Ma), 550–1429 Ma (sub-peaks at 614 Ma, 828 Ma and 942 Ma) and 1345–3204 Ma (sub-peaks at 1773 Ma and 2480 Ma). These zircons were mainly derived from the western Kunlun Mountain Range and northern Pamir salient to the west and south. The evolution of the provenance and source-to-sink relationship patterns in the southwestern Tarim Basin can be divided into three stages: (1) The Middle Eocene to Lower Oligocene sediments display a wide variety of detrital zircon ages, suggesting that the source area was extensive. (2) A major change in provenance occurred during the Late Oligocene to Early Miocene and was characterized by an abrupt increase in the proportion of Triassic and Lower Paleozoic igneous components, implying a significant adjustment in topography induced by the initial uplift and exhumation of the western Kunlun Mountain Range and northern Pamir salient. (3) In the Late Miocene, the source-to-sink system transformed again, and contributions of Triassic to Lower Paleozoic material weakened substantially due to the sufficient indentation of the Pamir salient. Our integrated analyses of zircon geochronology indicate that the main source terranes of the Paleogene and Cretaceous igneous detritus are the central and southern Pamir salient, respectively, which are speculated to have been continuously connected to the study area during Eocene-Pliocene times, although such detritus is scarce in certain formations and has not yet been detected.